Control Architecture for Cascaded H-Bridge Inverters in Large-Scale PV Systems. (July 2018) - Sridhar, V.; Umashankar, S.; Sanjeevikumar, P.; Ramachandaramurthy, Vigna K.; Mihet-Popa, Lucian; Fedák, Viliam
Abstract: An H-bridge along with the auxiliaries is the fundamental power module to build the cascaded H-bridge (CHB) inverter. In this paper, the design of basic building block of CHB inverter for PV applications with bypassing feature is discussed. Independent MPPT controls of each PV array at module level are proposed in this work. Instead of processing entire controls in one processor, different stages of controls and distributed processing of various functions of the system are proposed to improve the speed of computation. With this control architecture, hardware requirements of the individual processor cards also reduced. Functionalities of each controller card namely module level control card, phase-level control card, and master controller cards are explained in detail. Detailed interfacing and signal exchange between H-Bridge modules and the other controller cards are also presented. Simulation results are presented to verify the operation of the system with the proposed control architecture.